INVENTORY OF USUAL AND USUAL-LEGITIMIZED MODELS OF PRODUCTION OF NON-VERBALIZERS OF HYBRID RUSSIAN-UKRAINIAN WAR OF 2014–2024 - ДЮКАР, Катерина (Київський національний університет імені Тараса Шевченка, 2024)
The article examines the most common models and types of neo-verbalizer production of the hybrid 2014–2024 Russian-Ukrainian war based on the Ukrainian-language segment of social network and media content. It is emphasized that in the study innovation is interpreted as a hyperonym, to which the hyponyms “neo-derivative” and “neo-verbalizer” are subordinated. The focus of attention is on the units formed on the basis of usual and usual-legitimized patterns. The analysis of the study material shows a high level of neogenicity. The range of extracted innovations indicates that innovations are often produced with varying degrees of deviation from the norm or usage, as well as with non-usual wordformation tools. The author notes a gradation from structural and semantic conformity of innovations to various degrees of deformation within word-formation models. There has been a recent tendency to legitimize new usage models that emerge on the basis of deformed common language patterns. Not only is there an atypical compatibility of the formative bases and formants, but also the expansion of the latter’s meanings through the layering of additional shades of meaning. The cases of extreme deviations of models involving formants from other code systems, mainly English, are described. It is established that innovations actively enter into word-formation relations, in which the level of word-formation tact is not significant and requires a comprehensive consideration of the entire chain. Some neo-verbalizers reach the top of word-formation nests. It is pointed out that the most productive and regular are the models producing suffix and prefix innovations of various part-of-speech nature, although combined word-formation types are also involved. The activation of an affixed word formation over the past ten years has been observed. The production of new units by means of pure or suffixation-related stem formation is demonstrated. It has been observed that word formation in the general range of innovations is represented by a smaller number of derivatives. Neogenicity within the militaristic discourse is not limited to these types, which is illustrated by means of inflectional innovations.

Стаття присвячена розгляду найбільш поширених моделей і типів продукування неовербалізаторів гібридної російсько-української війни 2014–2024 років на матеріалі українськомовного сегмента соціальних мереж і медіаконтенту. Увага акцентована на тому, що в розвідці інновація тлумачиться як гіперонім, якому підпорядковані гіпоніми «неодериват» і «неовербалізатор». У фокусі уваги перебувають одиниці, утворені за узуальними й узуально легітимізованими зразками. Аналіз фактичного матеріалу свідчить про високий рівень неогенності. Масив вилучених інновацій указує на те, що нові одиниці часто продукуються з відхиленнями від норми чи узусу, а також за допомогою власне неузуального словотвірного інструментарію. Встановлена градація від структурно-семантичної відповідності інновацій узусу до різного ступеня деформацій у межах словотвірних моделей. Останнім часом оприявнюється тенденція до легітимізації в узусі нових моделей, які постають на базі деформованих загальномовних зразків. Відзначена не лише атипова сполучуваність твірних основ і формантів, а й розширення значень останніх через нашарування додаткових відтінків значення. Описані випадки екстремальних девіацій моделей, до яких залучаються форманти з інших кодових систем, переважно англійської мови. Установили, що інновації активно вступають у словотвірні стосунки, де рівень словотвірного такту є непоказовим і потребує комплексного розгляду всього ланцюжка. Деякі неовербалізатори стають вершинами словотвірних гнізд. Указали на те, що найбільш продуктивними та регулярними є моделі, за якими утворюються суфіксальні та префіксальні інновації різної частиномовної належності, хоча залучаються й комбіновані словотвірні типи. Засвідчена активізація афіксоїдного словотвору протягом останніх десяти років. Продемонстроване продукування нових одиниць шляхом чистого чи ускладненого суфіксацією основоскладання. Спостерегли, що словоскладання в загальному масиві інновацій репрезентоване меншою кількістю похідних. Згаданими типами неогенність у межах мілітаридискурсу не обмежується, що унаочнено за допомогою конфіксальних інновацій.
ІНВЕНТАРИЗАЦІЯ УЗУАЛЬНИХ І УЗУАЛЬНО ЛЕГІТИМІЗОВАНИХ СПОСОБІВ ПРОДУКУВАННЯ НЕОВЕРБАЛІЗАТОРІВ ГІБРИДНОЇ РОСІЙСЬКО-УКРАЇНСЬКОЇ ВІЙНИ 2014–2024 РОКІВ
Keywords: девіація; деформація моделі; інновація; неовербалізатор; неогенність; полімотиват; узуально легітимізована модель; innovation; deviation; model deformation; polymotivate; usually legitimized model; neo-verbalizer; neogeneity